Paleocene/Eocene carbon feedbacks triggered by volcanic activity - Kender, S; Bogus, K; Pedersen, GK; Mather, T (Springer Nature, 2021)
The Paleocene–Eocene Thermal Maximum (PETM) was a period of geologically-rapid carbon release and global warming ~56 million years ago. Although modelling, outcrop and proxy records suggest volcanic carbon release occurred, it has not yet been possible to identify the PETM trigger, or if multiple reservoirs of carbon were involved. Here we report elevated levels of mercury relative to organic carbon—a proxy for volcanism—directly preceding and within the early PETM from two North Sea sedimentary cores, signifying pulsed volcanism from the North Atlantic Igneous Province likely provided the trigger and subsequently sustained elevated CO2. However, the PETM onset coincides with a mercury low, suggesting at least one other carbon reservoir released significant greenhouse gases in response to initial warming. Our results support the existence of ‘tipping points’ in the Earth system, which can trigger release of additional carbon reservoirs and drive Earth’s climate into a hotter state.